L’agir enseignant vu par des collégiens : entre doxas et expertise - Audrey Boulin; Marie-Sylvie Claude (Recherches en Éducation)
This article is based on a survey of thirty students of “quatrième” who were asked to analyze the teachers’ performance after watching two video sequences showing the teachers working with different success in the same class of « troisième ». An analysis of the students’ interviews in relation to the “multi-agenda” of the teachers (as defined by Dominique Bucheton and his team), revealed three types of teaching analysis whether or not the surveyed students were working in the four categories of Bucheton’s model and whether or not they took into account what the filmed students learned with the teachers. The study suggests that while college students are adept at analyzing teachers’ filmed performance, the forms of assessment they use to do so are clearly differentiated.